DETERMINAN TINGKAT SUKU BUNGA, INDEKS DOW JONES, NIKKEI 225, DAN STRAITS TIME TERHADAP ISSI - Wibowo, Febrian Wahyu (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2019)
Islamic financing is a kind of investment that has system and operational based on sharia principles. Islamic financing is supervised by the Sharia Supervisory Board (DPS). This is to safeguard that there are no commercial involved such as gambling, usury, and prohibitedproducts. The indexfluctuation in the capital market of a country is influenced by world capital market indices. The first Islamic index in world is the Dow Jones Islamic Market Index (DJIM). Based on the discussion about the influence of Interest Rate variables, Dow Jones Islamic Market, Nikkei 225 Index, and Straits Times Index on the Indonesian Sharia Stock Index variable for June 2012 until March 2017Â  the conclusions are as follows: Interest Rate has a negative effect on the Indonesian Sharia Stock Index, Dow Jones Islamic Market has a positive effect on the Indonesian Sharia Stock Index, the Nikkei 225 has a negative effect on the Indonesian Sharia Stock Index, the Straits Times negatively affects the Indonesian Sharia Stock Index